NECESSARY CONDITION FOR THE EXISTENCE OF SOLUTIONS OF A WEAKLY NONLINEAR BOUNDARY-VALUE PROBLEM WITH IMPULSIVE ACTION - Шегда, Любов Михайлівна (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
We have obtained necessary condition for existence of solution of a weakly nonlinear degenerated boundary-value problem for a system of ordinary differential equations with impulsive action.